Financial markets and the challenges of sustainable growth - Małgorzata Janicka (Comparative Economic Research. Central and Eastern Europe, 2016)
Sustainable growth and responsibility for the economy and the environment are postulates rarely associated with the term "financial market". Financial markets are identified with the ruthless maximisation of profit at acceptable risk, rather than with socially responsible conduct. However, in the global economy businesses modify their priorities and become aware of not just the need to grow in financial terms but also to improve their quality performance. International financial markets have become part of this trend and are increasingly often adopting environmentally friendly attitudes and embracing the challenges posed by the concept of sustainable growth. Ideas such as CSR - Corporate Social Responsibility - and SRI - Socially Responsible Investment are gaining in importance. While sustainable growth of the economy as perceived from the point of view of the manufacturing or service sectors is widely discussed, the sustainable growth of financial markets is a relatively new concept and the available literature on "green" financial markets is quite scarce. This paper is intended to fill in this gap and examine the changes that have taken place on financial markets in the context of the idea of sustainable growth, with particular attention paid to the European Union markets.
Keywords: 330; financial market; European Union; sustainable growth; environmental measures